Utilizing the focused conversation method in qualitative public health research: a team-based approach - Charissa Fritzen-Pedicini; Susan C. Bleasdale; Lisa M. Brosseau; Donna Moritz; Monica Sikka; Emily Stiehl; Rachael M. Jones; for the CDC Prevention Epicenter Program (BMC, 2019)
Abstract Background Qualitative research studies are becoming increasingly necessary to understand the complex challenges in the healthcare setting. Successfully integrating interdisciplinary teams of investigators can be challenging, as investigators inherently view data through their disciplinary lens. Thus, new methods, such as focused conservation, are needed to facilitate qualitative data analysis by interdisciplinary teams. The purpose of this manuscript is to provide a clear description of how we implemented the focused conversation method to facilitate an organized data-driven discussion that responded to our study objectives and ensured participation of our interdisciplinary team. The focused conversation method has not, to our knowledge, been utilized for this purpose to date. Methods To better understand the experience of healthcare personnel (HCP) during preparations for the 2014-2015 Ebola Virus Disease (EVD) outbreak, we interviewed HCP who participated in decision making about EVD preparations and training of workers in the use of enhanced personal protective equipment ensembles in the metropolitan Chicagoland area of Illinois to attain a priori research objectives. We identified a systematic method - the focused conversation method - that enabled our interdisciplinary team to interactively contribute to the framing, analysis and interpretation of the data that would enable us to focus on our research objectives. Results The focused conversation developed to support our a priori research objective about the training of HCP in preparations included objective, reflective, interpretive and decisional questions. These questions grounded the conversation in the data, while leveraging discipline-specific lenses and professional experience in the analysis and interpretation. Insights from the conversation were reviewed later against interview transcripts to ensure validity. The conversation identified areas for future research directions and deficiencies in the interview instrument. Conclusions The focused conversation is an efficient, organized method for analysis of qualitative data by an interdisciplinary team.